1983
DOI: 10.3758/bf03202864
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus-response compatibility affects auditory Stroop interference

Abstract: The contribution of stimulus-response compatibility to Stroop interference was tested in an auditory version of the Stroop test. The words "high" and "low" were presented in high and low pitches with either the pitch or the word designated as the relevant dimension. College students categorized the relevant stimulus dimension with a verbal response, a buttonpress, or a pitched hum. Significant interference occurred in the incompatible conditions (pitch-verbal, word-hum, pitch-button), but not in the compatible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
67
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 30 publications
6
67
1
Order By: Relevance
“…The present results replicate the findings of McClain (1983) and Zakay and Glicksohn (1985) for a different paradigm . It was shown that when both dimensions of a stimulus have compatible responses , the interference produced by stimulus incongruity varies depending on the degree of SRC.…”
Section: Iloosupporting
confidence: 92%
See 2 more Smart Citations
“…The present results replicate the findings of McClain (1983) and Zakay and Glicksohn (1985) for a different paradigm . It was shown that when both dimensions of a stimulus have compatible responses , the interference produced by stimulus incongruity varies depending on the degree of SRC.…”
Section: Iloosupporting
confidence: 92%
“…It is possible to specifically examine the role of SRC in Stroop interference by increasing the degree of correspondence between the irrelevant stimulus dimension and the response (Flowers, Warner, & Polansky, 1979;McClain, 1983;Zakay & Glicksohn, 1985). Flowers et al (1979) had subjects classify either the numerosity or numeric values of digits or words; responses were indicated by oral naming, card sorting, manual tapping, or oral "tapping" in five separate experiments.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that incompatible responses produced substantially more negative priming (52 msec) than did compatible responses (16 msec). Since incompatible stimulusresponse mappings are associated with higher levels of Stroop-like interference (e.g., Fox, 1992;McClain, 1983), this pattern ofresults suggests that conditions associated with increased interference are also associated with increased negative priming. A second logical possibility is that interference and negative priming may be inversely related.…”
mentioning
confidence: 94%
“…Stroop's (1935) seminal research showed that the task of naming ink colors was slowed if each color of ink formed a color word that did not match the correct response. Most of the numerous studies further exploring that effect (reviewed recently by MacLeod, 1991MacLeod, , 1992 have provided conflicting cues within the visual modality (as Stroop did) or in a few cases within the auditory modality (Green & Barber, 1981;McClain, 1983). However, Cowan and Barron (1987) found that the task of naming visually presented colors was slowed by the concurrent presentation of an audiotape containing a random sequence of spoken color words drawn from the same set as the correct responses.…”
mentioning
confidence: 99%